Review of the genus Lemaireia Nässig & Holloway, 1988 from China, with description of a new species (Lepidoptera: Saturniidae) - Jiang, Zhuo-Heng; Wang, Cheng-Bin; Miu, Ben-Fu; Guo, Liang (Zootaxa, 2021)
A new species of the genus Lemaireia Nässig & Holloway, 1988 (Lepidoptera: Saturniidae: Saturniinae: Saturniini), L. daparo sp. n., is described from evergreen broad-leaf forests in Panzhihua (Sichuan), Qujing (Yunnan) and Dali (Yunnan) of China. The new species resembles L. luteopeplus aureopeplus Nässig & Holloway, 1988 and L. hainana Nässig & Wang, 2006 from China, but can be easily separated from them by the male genitalia. In addition, the genus Lemaireia is reported here for the first time from Sichuan Province, and now its distribution range reached the northeastern extreme point. The habitus, diagnostic characters and distribution map of the three species of the genus Lemaireia from China are provided. A list of all Lemaireia species presently known worldwide is also given.